Børnereddere DEN PRIVATE FILANTROPI OG BEHANDLINGEN AF KRIMINELLE OG FORSØMTE BØRN I DANMARK OMKRING ÅR 1900 - Løkke, Anne (Historisk Tidsskrift, 1991)
The first real child welfare law in Denmark was passed in 1905, empowering public authorities to remove children from their homes. Prior to the law lay a half century of philanthropical work with children and a decade of public debate and conflicting efforts to pass proper legislation. When the law was finally passed, it could claim support along the whole political spectrum from the Social Democrats to the Party of the Right. The present study approaches the subject from the viewpoint of mentality and social history, seeking primarily to elucidate the broader and long-term development of relationships between children, parents, the general public, and the public authorities that were reflected in the child welfare act. Noteworthy theoretical inspiration has been drawn from Norbert Elias’ civilisation critique, from Aries’ concept of childhood, and from recent mentality history research. On the basis of a three-level analysis (structure, class, and subject), the study identifies instances where group or individual initiatives resulted in an outcome directly contrary to the intentions of at least some of the initiators, even though the effect was but a logical consequence of their actions. The thesis of the study is that child welfare developed through the interplay of deliberate decisions and deeply rooted norms and conceptions. These more fundamental value judgments are identified on the basis of an analysis of the most important drafts of the bill and a detailed study of one of the most prominent philanthropical societies devoted to child welfare: The Christian Association for Saving Wayward Children. Particular effort is made to depict the society’s weltanschauung, the values that permeated its everyday work, and the conceptions that emerge from its deliberations. The study looks for the »child savers« answers to questions like these: When is a child on the road to crime? Why is the removal of a child from its home a cure for burgeoning criminals? How do you define a neglected child? How do you describe a good childhood? The most important concept for understanding the Christian Association is social control. Much of the motivation and energy that went into its work was a fear of social disintegration and chaos, the fear that whole generations of the lower classes would grow into adulthood bereft of respect for the social order. Anxieties were not necessarily grounded in any real social breakdown, but in an interpretation of social trends as signs of a disintegration. In the course of the last half of the nineteenth century a change of perception occurred with regard to juvenile petty theft, truancy, loitering, ill disciplined, noisy or annoying behaviourin public piaces and the like. These things were gradually seen as evidence of a lack of proper upbringing among working class children, indications that they were on the road to a life of crime. The Christian Association shared this view of juvenile misdemeanours, but was repulsed by the harsh treatment meted out to children by the criminal code. Neither rod nor prison would better a child’s behaviour, the society claimed, because it traced the source of the evil to incompetent parents who lacked both the will and the ability to give their children a childhood created in the image of a middle class home. The best cure, they concluded, was to provide the wayward child with such a home. The social control angle is nevertheless only part of the explanation of the society’s endeavours. Mercy - to use the term of the times - was also an important aspect. The origins and success of the society are testimony to the sentimentality and sensitivity that pervaded conceptions of what a child should be exposed to. A common trait among many of the society’s wards was that they came from the very poorest of the lower classes; they as well as their families were desperately in need of help. Prior to 1905 clients had a certain position of strength vis-å-vis the society, because children could not be removed from their homes against their parents’ will. Parents had the legal choice of accepting og declining the society’s offer, whatever the real coercion of their economic situation. The society’s conception of a child inevitably dictated an offer to remove the child from its parents. A child was conceived as basically good, whence its evil tendencies had to be the products of its parents’ failures and a bad environment. It was also of significance that the society was imbued with a medical and hygienic mentality that led it to view children as potential bearers of moral disease. A moral »epidemic« could therefore be contained by quarantining those who were already infected. Translated by Michael Wolfe